2012
DOI: 10.2215/cjn.00770112
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Outcomes of BK Virus Allograft Nephropathy among ABO- and HLA-Incompatible Kidney Transplant Recipients

Abstract: SummaryBackground and objectives ABO-incompatible kidney transplant recipients may have a higher incidence of BK virus allograft nephropathy (BKVAN) compared with ABO-compatible recipients. It is unclear whether HLAincompatible recipients share this risk or whether this phenomenon is unique to ABO-incompatible recipients.Design, setting, participation, & measurements This study analyzed adult incompatible kidney transplant recipients from 1998 to 2010 (62 ABO-incompatible and 221 HLA-incompatible) and identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
72
2
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 35 publications
6
72
2
2
Order By: Relevance
“…There were 28 patients who received an ABO-incompatible allograft during the same study period. There was less BKV viremia in patients undergoing ABO-incompatible transplant (3.5% vs. 20%; P=0.03) which is different from what was previously reported (2). This is interesting because both HLA-sensitized and ABO-incompatible recipients undergo a similar regimen and maintenance immunosuppression.…”
contrasting
confidence: 68%
See 1 more Smart Citation
“…There were 28 patients who received an ABO-incompatible allograft during the same study period. There was less BKV viremia in patients undergoing ABO-incompatible transplant (3.5% vs. 20%; P=0.03) which is different from what was previously reported (2). This is interesting because both HLA-sensitized and ABO-incompatible recipients undergo a similar regimen and maintenance immunosuppression.…”
contrasting
confidence: 68%
“…We have previously demonstrated that patients who are desensitized just before surgery (plasma exchange with low dose IVIGTrituximab/splenectomy) have higher rates of BK nephropathy compared to compatible kidney allograft recipients (2). In this retrospective analysis of a prospectively maintained cohort, ABO-incompatible (n=62) and HLA-incompatible (transplantation across preformed donor-reactive antibodies, n=221) kidney allograft recipients had BK nephropathy rates of 17.7% and 5.9%, respectively (compared to 3.0% in compatible kidney allograft cohort).…”
mentioning
confidence: 99%
“…quoted previously, the absence of HLA C7 among both donors and recipients was highlighted as a factor contributing to sustained BK viremia in the recipients. Sharif et al . reported that ABO‐incompatible RTR were at higher risk of developing BKVN compared with HLA‐incompatible kidney transplants.…”
Section: Bk Virus Nephropathymentioning
confidence: 99%
“…reported that ABO‐incompatible RTR were at higher risk of developing BKVN compared with HLA‐incompatible kidney transplants. They compared 221 HLA‐mismatched RTR with 68 ABO‐I RTR during 1998–2010 and found a BKVN prevalence of 5.9% v/s 17.5%, respectively ( P = 0.08) . Although more potent immunosuppression with thymoglobulin induction, the use of Tacrolimus (Tac) and Mycophenolate (MPA) seems to be associated with increased incidence of BKVN; the contribution of individual agents is controversial .…”
Section: Bk Virus Nephropathymentioning
confidence: 99%
“…Nonetheless, both recipient and donor factors have been implicated [4][5][6][7][8][9]. Nonetheless, both recipient and donor factors have been implicated [4][5][6][7][8][9].…”
Section: Risk Factorsmentioning
confidence: 99%